A multifunctional protein EWS regulates the expression of Drosha and microRNAs - Kim, K. Y.; Hwang, Y. J.; Jung, M-K; Choe, J.; Kim, Y.; Kim, S.; Lee, C-J; Ahn, H.; Lee, J.; Kowall, N. W.; Kim, Y. K.; Kim, J-I; et al. (NATURE PUBLISHING GROUP, 2014)
EWS (Ewing's Sarcoma) gene encodes an RNA/DNA-binding protein that is ubiquitously expressed and involved in various cellular processes. EWS deficiency leads to impaired development and early senescence through unknown mechanisms. We found that EWS regulates the expression of Drosha and microRNAs (miRNAs). EWS deficiency resulted in increased expression of Drosha, a well-known microprocessor, and increased levels of miR-29b and miR-18b. Importantly, miR-29b and miR-18b were directly involved in the post-transcriptional regulation of collagen IV alpha 1 (CoI4a1) and connective tissue growth factor (CTGF) in EWS knock-out (KO) mouse embryonic fibroblast cells. The upregulation of Drosha, miR-29b and miR-18b and the sequential downregulation of CoI4a1 and CTGF contributed to the deregulation of dermal development in EWS KO mice. Otherwise, knockdown of Drosha rescued miRNA-dependent downregulation of CoI4a1 and CTGF proteins. Taken together, our data indicate that EWS is involved in post-transcriptional regulation of CoI4a1 and CTGF via a Drosha-miRNA-dependent pathway. This finding suggests that EWS has a novel role in dermal morphogenesis through the modulation of miRNA biogenesis.
Keywords: TISSUE GROWTH-FACTOR; SARCOMA GENE EWS; COLLAGEN-IV; COMPLEX